2007
DOI: 10.1186/1471-2407-7-164
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of histopathology and trends in cervical cancer: a SEER population study

Abstract: Background: Histopathology is a cornerstone in the diagnosis of cervical cancer but the prognostic value is controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
171
4
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(188 citation statements)
references
References 66 publications
8
171
4
5
Order By: Relevance
“…Since some pathologic parameters are related to patients' prognosis, these parameters affect the plan of further treatment. [4][5][6] This means that pathologic findings of surgical specimens are important for the management of patients with cervical cancer. However, clinicians should consider preoperative diagnosis, because the stage of cervical cancer is clinically determined and clinicians can get much information related with prognosis from preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since some pathologic parameters are related to patients' prognosis, these parameters affect the plan of further treatment. [4][5][6] This means that pathologic findings of surgical specimens are important for the management of patients with cervical cancer. However, clinicians should consider preoperative diagnosis, because the stage of cervical cancer is clinically determined and clinicians can get much information related with prognosis from preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that histological type is an important prognostic factor (Nakanishi et al, 2000;Takeda et al, 2002;Vinh-Hung et al, 2007;Chen et al, 2008;Zivanovic et al, 2009;Lee et al, 2010;Park et al, 2010). A US study of patients from 1997 to 2003 in the SEER database found 5-year overall survivals of 32.5% for patients with SNEC, 74.3% for ADC and 64.6% for SCC (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining cases consist of rare histological types including small cell neuroendocrine carcinoma (SNEC) (Kosary, 1994;Farley et al, 2003). Over time, the rates of invasive SCC have declined, while the incidence of 5356 ADC (Smith et al, 2000;Wang et al, 2004;Mathew and George, 2009) and SNEC (Vinh-Hung et al, 2007) have increased. A previous US study based on the Surveillance, Epidemiology, and End Results (SEER) data revealed a 42% reduction in age-adjusted incidence rates of SCC from 1973-1977 to 1993-1996, while the age-adjusted incidence rates of ADC increased by 29%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations